2021
DOI: 10.2147/jpr.s306594
|View full text |Cite
|
Sign up to set email alerts
|

A Bibliometric Analysis of Research Trends of Acupuncture Therapy in the Treatment of Migraine from 2000 to 2020

Abstract: Background: Migraine is the second-leading cause of disability worldwide. It is often characterized by attacks of severe, mostly unilateral, pulsating headache associated with symptoms such as photophobia, phonophobia, nausea, vomiting, and cutaneous allodynia. Acupuncture therapy has been used worldwide for the treatment of migraine. However, no visual bibliometric analysis has been conducted on the effects of acupuncture on migraine over the past 20 years. Therefore, this study aimed to explore the current s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 63 publications
(107 reference statements)
1
22
0
Order By: Relevance
“…The results from this present bibliometric analysis are comparable to ndings from previous publications of research at the intersection in question. The rst bibliometric analysis at the intersection of acupuncture and migraine explored the Web of Science databased for articles on the use of acupuncture for migraine treatment published between 2000 and 2020 [24]. The annual number of publications they reported followed a similar trend to those found in the present study, however, the number of publications they reported from 2011 to 2020 were noticeably greater than the gures we reported.…”
Section: Comparative Literaturesupporting
confidence: 69%
“…The results from this present bibliometric analysis are comparable to ndings from previous publications of research at the intersection in question. The rst bibliometric analysis at the intersection of acupuncture and migraine explored the Web of Science databased for articles on the use of acupuncture for migraine treatment published between 2000 and 2020 [24]. The annual number of publications they reported followed a similar trend to those found in the present study, however, the number of publications they reported from 2011 to 2020 were noticeably greater than the gures we reported.…”
Section: Comparative Literaturesupporting
confidence: 69%
“…There was no restriction on language, and we retrieved 801 studies. After eliminating meeting abstracts (14), editorial material (18), book chapters (3), letters (11), corrections (1) and articles not related to the search topic (433), we included 321 records (see the Supplementary Material), including 255 articles and 66 reviews, for further visualization and analysis. We saved these papers in a text document and named it "download_txt."…”
Section: Data Collectionmentioning
confidence: 99%
“…A total of 333 authors have taken part in research on acupuncture in relation to cardiopathies (Figure 4). Fanrong Liang from Chengdu University of Traditional Chinese Medicine ranked first with 21 publications, followed by Cunzhi Liu (12), Shengfeng Lu ( 12), Yu Wang ( 12), Jingwen Yang (11), Guangxia Shi ( 9), Liqiong Wang (7), Bingmei Zhu (7), Peijing Rong (7), and Chunzhi Tang (6). A noteworthy feature of this outcome is that the centrality of the authors was relatively low (less than 0.10), indicating that these authors have not established a close and influential cooperative network (Table 4A).…”
Section: Authors and Co-cited Authorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower back pain acupuncture research is mostly from the USA and in the Journal of Alternative and Complementary Medicine (Liang et al, 2017). Migrainerelated acupuncture research is most published in the USA and in the headache journal Cephalalgia (Zhao, 2021). The USA also published the most acupuncture research in obstetrics and gynaecology (Wu et al, 2021).…”
Section: Acupuncturementioning
confidence: 99%